Особливості позачергових парламентських виборів у Австрії 2019 р. - Semenko, Vitalii (Chernivtsi National University, 2022)
The article deals with the peculiarities of the parliamentary elections in the Republic of Austria in 2019, as well as the main reasons for the success of the Green party, which not only managed to im- prove its election results, but also joined the ruling coalition with the Austrian People’s Party, led by and its young leader Sebastian Kurtz, the former Minister for Foreign Affairs and the OSCE Chair- man. The main consequences of the so-called political scandal of Ibizagate, which led to the reformat- ting of power in Austria, are highlighted. The main results of the elections to the lower house of parliament of the National Council, in which political parties overcame the 4 percent barrier, were analyzed in sufficient detail. The main conclu- sions of well-known domestic and foreign political scientists, experts, who assessed the reasons for the support of right-wing and alternative green political forces in European countries, and in particular in Austria, which received significant support in the elections, are characterized. Green parties are becoming more and more popular in the most European countries, not only be- cause they are pulling a part of the electorate from the socialists or nationalists, but also because envi- ronmental issues are increasingly worrying people, as well as the desire of green parties to become popular all-people’s parties. The Green parties are one of the main supporters of the sanctions policy towards Russia, they are supporters of sustainable development humanity on Earth, development based on the principles of respect for the rights human, environmental responsibility, freedom, justice, diversity and rejection from violence. As a result of the study, a prediction is made that in the future, the importance of the Greens in the Austrian party system will increase. Achieving sustainable eco- nomic development can be facilitated by the transition from traditional economic growth model to a green growth model.
A Snap 2019 Austrian Parliamentary Elections’ Peculiarities
Keywords: political parties, parliamentary elections; political parties, parliamentary elections